A Mechanism Exploration of Metabolic Syndrome Causing Nodular Thyroid Disease - Zexin Li; Lili Zhang; Yingshi Huang; Peixuan Yang; Wencan Xu (International Journal of Endocrinology)
Background. Metabolic syndrome (MS) and its components have been demonstrated to facilitate the prevalence of thyroid nodules (TNs). The underlying pathogenesis needs to be elucidated. Methods. A total of 2722 subjects, who underwent health checkup in our institute from December 2014 to November 2018, were retrospectively and randomly collected. After exclusion, 2068 subjects were chosen, and their anthropic and clinical data were collected. Results. After matching age, gender, uric acid (UA), and creatinine (Cr) by propensity score matching (PSM), subjects with MS had higher prevalence of TNs than those without MS, as well as higher thyroid-stimulating hormone (TSH) and inflammatory levels, indicated by the higher white blood cell (WBC), lymphocyte (LY), and monocyte/high-density lipoprotein (Mo/HDL). After matching age, gender, UA, Cr, TSH, free triiodothyronine (FT3), thyroxine (FT4), WBC, NE, LY, Mo, NE/LY, LY/Mo, and Mo/HDL by PSM, no significant difference of the prevalence of TNs was found between MS and non-MS groups. Step logistic regression suggested glucose intolerance (GI), among all the components of MS, was an independent impact factor of TNs and was considered to contribute most to the formation of TNs. The prevalence of TNs was higher in the GI group after matching age, gender, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood sugar (FBS), UA, Cr, triglyceride (TG), cholesterol (CHOL), HDL, and low-density lipoprotein (LDL). Conclusions. Patients with MS have a higher prevalence of TNs, probably due to the elevated TSH and inflammatory levels in vivo. Among the components of MS, glucose intolerance contributes most to the development of TNs.